Pengaruh Media Komik Bangun Datar terhadap Kemampuan Kognitif Peserta Didik dalam Pembelajaran Matematika di SD Negeri 136539 Tanjungbalai - Tia Anggraini Silalahi; Pangulu Abdul Karim; Nurdiana Siregar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study, entitled "The Effect of Flat Shape Comic Media on Students’ Cognitive Abilities in Mathematics Learning in Elementary Schools 136539 Tanjungbalai," aimed to determine the effect of using comics in learning flat shapes on the cognitive abilities of second-grade students at SD Negeri 136539, Tanjungbalai. This study used a quantitative method with a quasi-experimental design of the two-group pretest-posttest type. The research subjects consisted of 20 students divided into two groups, namely the experimental group using comic media and the control group using conventional methods, each consisting of 10 students. The instrument used was a multiple-choice question that had been tested for validity and reliability. The results of the normality and homogeneity tests showed that the data were normally distributed and homogeneous. The independent t-test showed a significant influence between the experimental and control groups with a significance value. The average learning outcomes of the experimental group were higher than those of the control group. This indicates that comics have a positive effect on improving students' cognitive abilities. Comics present material in a visual, engaging, and contextual manner, making it easier to understand. Therefore, comics can be an effective alternative learning medium.